Classification challenges of the 2019 revised International Standards for Neurological Classification of Spinal Cord Injury (ISNCSCI) - Kirshblum, Steven; Schmidt Read, Mary; Rupp, Rüdiger (Spinal cord, 2022)
Retrospective review of ISNCSCI datasets.